Improvement of Mosfet Characteristics - Ranbir Singh (Active and Passive Electronic Components)
By inclusion of a semi-dielectric layer, a novel MOSFET Structure, the T-MOSFET, and its integrated circuit version are presented. Both for the enhancement mode and the depletion mode, equivalent circuit models are developed. Also, the high frequency behaviour is explained by a model and the behaviour of a T-MOSFET under different conditions is given.